A case study of computer application in PDRM : with special focus on PDRM headquarters in Bukit Aman / Norhayati Izhar - Izhar, Norhayati (2006)
This research is the analysis of computer application in PDRM (Polls Diraja Malaysia) Bukit Aman. In the agency have currently used the computer technology, but this research is to identified the type of computer used, the application areas, and the computer applications used in the identified application areas. From the interview, have founded there are several types of computer used in the agency with different operating system and other characteristics. From the interview also have found that there are several systems that used in the agency. The systems is used whether routinely or non-routine based on the application areas. The best recommendation is where the agency must upgrade the computer system and develop more systems as the application in the agency.